Critique of Ecological Jurisprudence and Environmental Ethics Regarding the Relocation of the National Capital - Fahmi Kurniawan; Imam Nururi; M. Guntur Sandi Pratama (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
This study aims to critically examine the IKN relocation through the lens of Islamic ecological jurisprudence (fiqh al-bi’ah) and Islamic environmental ethics, by exploring the values of maqāṣid al-sharī‘ah and the principles of ecological spirituality as articulated by Seyyed Hossein Nasr. The research employs a qualitative method using a literature review approach, with prescriptive analysis of Islamic legal sources, scientific journals, environmental reports, and statutory regulations. The findings indicate that the IKN project potentially violates principles of ecological sustainability and neglects key Islamic values such as the prohibition of harm (lā ḍarar wa lā ḍirār), maintaining balance (mīzān), and the human responsibility as khalīfah (steward) of the Earth. Nasr interprets the ecological crisis as a manifestation of a deeper spiritual crisis, wherein modernity has severed humanity’s connection to the sacredness of nature. Islamic ecological jurisprudence and environmental ethics offer a new paradigm for development rooted in spiritual values, treating nature as an intrinsically valuable entity rather than a mere resource for exploitation. This study asserts that the IKN project requires deep ethical and ecological considerations to ensure long-term sustainability, including the involvement of Indigenous communities, forest conservation, and adherence to the principles of ecological justice within the Islamic worldview.